2016
DOI: 10.1016/j.bbamcr.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of Mg2+ transport proteins during Parkinson's disease-like dopaminergic cell degeneration in PC12 cells

Abstract: Mg(2+) is an essential cation to maintain cellular functions, and intracellular Mg(2+) concentration ([Mg(2+)]i) is regulated by Mg(2+) channels and transporters. In our previous study, we demonstrated that MPP(+) elicits Mg(2+) influx across the cell membrane and Mg(2+) mobilization from mitochondria, and the resulting [Mg(2+)]i is an important determinants of the cell viability in MPP(+) model of Parkinson's disease (PD). It indicates that cellular Mg(2+) transport is one of the important factors to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Actually, cells possess several Mg 2+ transporting systems [37,167], and Mg 2 + homeostasis is robustly maintained through the compensation mechanism in vertebrates. In fact, the expressions of several Mg 2+ transporters are simultaneously and dynamically changed in response to the cellular environments [168]. The properties of TRPM7 as the channel and kinase and compensatory maintenance of Mg 2+ homeostasis causes the difficulties for revealing the roles of Mg 2+ in animal developments.…”
Section: Effects Of Mg2+ On the Cellular Fate And Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Actually, cells possess several Mg 2+ transporting systems [37,167], and Mg 2 + homeostasis is robustly maintained through the compensation mechanism in vertebrates. In fact, the expressions of several Mg 2+ transporters are simultaneously and dynamically changed in response to the cellular environments [168]. The properties of TRPM7 as the channel and kinase and compensatory maintenance of Mg 2+ homeostasis causes the difficulties for revealing the roles of Mg 2+ in animal developments.…”
Section: Effects Of Mg2+ On the Cellular Fate And Phenotypementioning
confidence: 99%
“…The suppression of Mg 2+ influx decreases the viability of MPP + -exposed cells, and cell viability is highly correlated with [Mg 2+ ] cyto [39]. Moreover, the MPP + -induced inhibition of mitochondria itself altered the expression levels of cellular Mg 2+ -transporting proteins [168]. A 6-hydroxydopamine (6-OHDA)-induced PD animal model revealed lower levels of the SLC41A1 expression [204] and Mg 2+ [205] compared with control rats.…”
Section: Neuropathology Of Mg2+ Homeostasismentioning
confidence: 99%
“…Decreased SLC41A1 expression/activity might decrease the SLC41A1-dependent magnesium recycle of cells, thus causing hypomagnesemia, and decreasing the free intracellular Mg 2+ in cells 33 . Experimental evidence based on the PD-like dopaminergic cell line PC12 showed that free intracellular Mg 2+ protected cells from damage of oxidant stress, and expression deficiency of magnesium transporter protein could significantly attenuate the oxidation resistance, thus increasing the susceptibility of neurodegenerative diseases including PD 34 . In all, Mg 2+ homeostasis regulated by SLC41A1 may play an important role in PD prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, significant loss of dopaminergic neurons in the substantia nigra, similar to the loss seen in Parkinson’s disease, was elicited merely by feeding them a low-magnesium diet for two generations [ 7 ]. In contrast, Mg 2+ supplementation or overexpression of the Mg 2+ channel have neuro-protective effects on cellular and animal models of Parkinson’s [ 8 , 9 , 10 ] and Alzheimer’s diseases [ 11 ]. These evidences show that Mg 2+ is intricately involved in nervous system functioning and neuroprotection.…”
Section: Introductionmentioning
confidence: 99%